STRUCTURAL IMBALANCES OF ECONOMIC DEVELOPMENT OF REGIONS IN UKRAINE - Melnyk, Alla (Journal of European Economy, 2017)
The problem of structural imbalances elimination of economic development of regions in Ukraine is raised. It is determined that the starting point of the analysis of the regional economies structure is to assess its potential. The evaluation of the economic potential of regions has been made. The comparison of natural-material composition of the economic potential and its structural contribution into the socio-economic development indicators showed the imbalances of economic structure of regions. On the basis of territorial concentration of resources there are identified the root causes of deformations in the structure of the economy of certain regions.The structure of regional economies was examined in the context of major structural dimensions in the dynamics and statics. The conclusion about the existence of disproportionality was made. Also the relevance of increasing the role of authorities in structuring of regional economies was corroborated. The necessity of forming selective policies of structural adjustment of regional economies and the criteria for the development strategy was proposed. On the example of Ternopil region the priorities of regional structural policy was corroborated.